LAS DIFERENCIAS ENTRE LA EDUCACIÓN A DISTANCIA Y VIRTUAL EN COLOMBIA - Sandra Naranjo (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2021)
The article presents the conceptual differences around distance and virtual educational modalities in Colombia, analyzingthe legal context under Law 30 of 1992 and Decree 1295 of 2010 that established two modalities in distance education:traditional distance and distance education. In addition, Decree 1075 of 2015 and 1280 of 2018 as a regulatoryframework for higher education and its modalities, on the other hand, a historical journey is made highlighting theincidence of technological development, the use of ICT, offer of programs and indicators evaluation of the quality of bothmodalities.